2022
DOI: 10.3390/su142416719
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation on Plastic Waste Issues and Plastic Disposal Strategies to Protect the Environment: A UAE Perspective

Abstract: Due to the rise in waste, both developed and developing countries’ municipal solid waste (MSW) disposal systems are overburdened. The increased inflow of used plastic water bottles has rendered the situation difficult. Plastic usage in several forms is becoming indispensable in daily life, despite its harmful effects on humans and animals in general. Government bodies are eager to cut plastic usage in several forms, but the manufacturing costs and selling prices make it difficult to replace plastic with materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Similarly, the finding of the study supports Osibanjo and Nnorom (2007) who investigated the practices of plastic waste generation and management in three urban areas of Nigeria and reported that a significant amount of plastic waste production, insufficient infrastructure for waste collection and disposal, and a restricted level of public knowledge regarding the ecological implications of plastic waste in Nigeria. Abu Jadayil et al (2022) have reported a significant increase in the utilization of plastic for water packaging in recent times. This is evidenced by the prevalence of plastic bottle waste in various communities and the shared desire among individuals in both developed and developing nations for remedial action.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Similarly, the finding of the study supports Osibanjo and Nnorom (2007) who investigated the practices of plastic waste generation and management in three urban areas of Nigeria and reported that a significant amount of plastic waste production, insufficient infrastructure for waste collection and disposal, and a restricted level of public knowledge regarding the ecological implications of plastic waste in Nigeria. Abu Jadayil et al (2022) have reported a significant increase in the utilization of plastic for water packaging in recent times. This is evidenced by the prevalence of plastic bottle waste in various communities and the shared desire among individuals in both developed and developing nations for remedial action.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Importantly, the commonly adopted disposable face masks are manufactured from petrochemical-based plastic materials, such as polypropylene, polystyrene, polycarbonate, polyethylene, or polyester. These materials, as they wither, can enter into the food chain, thereby presenting a secondary public health challenge [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…If no measures are taken, it is estimated that by the year 2030, the quantity will increase to two trucks per minute, and by 2050, it will reach four trucks per minute [2,3]. Finding solutions for the elimination or environmentally friendly reuse of these waste materials is necessary [4].…”
Section: Introductionmentioning
confidence: 99%